1996
DOI: 10.2114/jpa.15.169
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Women during Exercise under Dry-Heat Condition in Winter and Summer.

Abstract: Fourteen young Japanese women were exposed to a dry-heat condition (Ta = 40 degrees C, rh = 30%) both in winter and summer. During an exposure for 110 min, they were rested on a bicycle ergometer for 20 min, exercised with an intensity of 40% Vo2 max for 60 min and recovery for 30 min. Their rectal and skin temperatures, and heart rate were determined every minute. Total sweat loss and dripping sweat were recorded throughout the experiment by independent bed balances which connected to a computer processor wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…The baseline, mean, and peak HR were lower in summer than winter, in the CON condition, which is consistent with research that reported a lower resting HR in summer than winter (by 5 bpm) in participants, in a thermoneutral climate chamber (25°C, 50% RH; [ 32 ]). Keatisuwan and colleagues (1996) similarly reported that the resting HR of participants following seasonal acclimatization was 9 bpm lower in summer than in winter [ 23 ], the same as the reduction in baseline HR that was noted in our study. The resting HR values in summer in the aforementioned studies were 74 bpm [ 32 ] and 71 bpm [ 23 ], whereas the mean, baseline HR value in summer in our study was 85 bpm.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The baseline, mean, and peak HR were lower in summer than winter, in the CON condition, which is consistent with research that reported a lower resting HR in summer than winter (by 5 bpm) in participants, in a thermoneutral climate chamber (25°C, 50% RH; [ 32 ]). Keatisuwan and colleagues (1996) similarly reported that the resting HR of participants following seasonal acclimatization was 9 bpm lower in summer than in winter [ 23 ], the same as the reduction in baseline HR that was noted in our study. The resting HR values in summer in the aforementioned studies were 74 bpm [ 32 ] and 71 bpm [ 23 ], whereas the mean, baseline HR value in summer in our study was 85 bpm.…”
Section: Discussionsupporting
confidence: 86%
“…Keatisuwan and colleagues (1996) similarly reported that the resting HR of participants following seasonal acclimatization was 9 bpm lower in summer than in winter [ 23 ], the same as the reduction in baseline HR that was noted in our study. The resting HR values in summer in the aforementioned studies were 74 bpm [ 32 ] and 71 bpm [ 23 ], whereas the mean, baseline HR value in summer in our study was 85 bpm. That could mean that the staff were simply fitter in summer, as regular exercise and physical activity can cause a reduction in resting HR [ 33 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Understanding the aforementioned criteria on body heat balance, the magnitude of heat stress in hot (warm) and humid environments has been studied, for example, by Niwa and Nakayama (1978), Smolander and Holmér (1991), Kondo et al (1996), Keatisuwan et al (1996), Maughan et al (2012), and Shen and Zhu (2015). In exercise physiology considering thermal environments, the primary purpose is supposed to be evaluation of changes in exercise capacity or performance in hot and humid environments, where Eskmax becomes minimal because heat loss from the human body is limited.…”
Section: Studies On Exercise Physiologymentioning
confidence: 99%
“…In exercise physiology considering thermal environments, the primary purpose is supposed to be evaluation of changes in exercise capacity or performance in hot and humid environments, where Eskmax becomes minimal because heat loss from the human body is limited. Under these specific situations, the magnitude of heat stress can be clearly estimated if individual and seasonal differences in sweating capacity (Keatisuwan et al, 1996) and heat acclimatization (Shen and Zhu, 2015) can be disregarded. In other words, accumulated knowledge on individual and seasonal differences in sweating capacity and heat acclimatization may depend on future studies to predict the magnitude of heat stress for various populations.…”
Section: Studies On Exercise Physiologymentioning
confidence: 99%